Design Considerations of Structural Parameters in Resonant Tunneling Diode by None-Equilibrium Green Function Method - M. Charmi; M.H. Yousefi (Журнал нано- та електронної фізики)
This paper presents the effects of structural parameters like Quantum well width, barrier width, spacer width, contact width and contact doping, on performance of Resonant Tunneling Diode using full quantum simulation. The simulation is based on a self-consistent solution of the Poisson equation and Schrodinger equation with open boundary conditions, within the non-equilibrium Green’s function formalism. The effects of varying the structural parameters is investigated in terms of the output current, peak current, valley current, peak to valley current ratio and the voltage associated with the peak current. Simulation results illustrate that the device performance can be improved by proper selection of the structural parameters.